Menstrual cycle related shifts in personality and cognitive measures of masculinity: relation to mate value - Hromatko, Ivana; Tadinac, Meri; Vranić, Andrea (2007)
Numerous studies have shown that variations in sex hormones across the menstrual cycle influence cognition on various levels: from perception of opposite-sex faces to efficacy in solving sex-biased tasks. The aim of this study was to explore (a) whether masculinity and femininity as personality traits also vary during menstrual cycle ; (b) whether masculinity and femininity predict shifts in efficacy of solving sex-biased cognitive task across the menstrual cycle ; and (c) the relation between masculinity/femininity and mate value. One repeated measures study, and two cross-sectional studies were conducted, using Bem Sex Roles Inventory (BSRI) as a measure of masculinity and femininity, Spatial Relations Test as a measure of (sex-dimorphic) cognitive ability to understand spatial relations, and Mate Value Inventory as a measure of person's value on the partner market. 60 healthy young women with regular menstrual cycles and not using oral contraceptives participated in the Study 1. BSRI was modified, in the way that that instead of the usual question "How often do you behave like that?" pertaining to every item, participants had to answer the question "Did you behave like that in the last 5 days?". In the Study 2, 22 young healthy women with regular menstrual cycles were tested twice (during fertile and non-fertile phases of the cycle) with Spatial Relations Test. In the Study 3, 101 women filled out the BSRI and the Mate value Inventory. Study 1 showed that there were no differences in femininity scores among different phases of menstrual cycle, while masculinity scores varied significantly: women scored higher on masculine items during late follicular (fertile) phase, compared to any other phase of the menstrual cycle. Study 2 showed that women with higher masculinity scores had a greater menstrual cycle-related shift in Spatial Relations Test, while femininity did not correlate with the amplitude of shift. In Study 3, the regression analysis with masculinity and femininity scores as predictor variables, and mate value as a criterion variable showed that both masculinity and femininity account for a significant proportion of variance of mate value. The finding that (a) masculinity is most pronounced during fertile period, (b) masculinity predicts shifts in cognitive ability across menstrual cycle, and (c) both masculinity and femininity contribute to mate value suggest that there might be a hormone mediated evolved psychological mechanism making a woman more assertive and dominant during short time-window when a conception is likely.
Projekt MZOS
Projekt MZOS
ENG